Improving Students' Problem-Solving Skills Using The Problem-Based Learning (Pbl) Model In Pancasila Education Material For Grade Viii Chapter 1 Pancasila In My National Life In Class Viii.E At Smp Negeri 1 Sewon - Siti Komariyah; Mukhamad Murdiono (Journal of World Science, 2025)
This research aims to improve the problem-solving ability of students in grade VIII.E SMP Negeri 1 Sewon through the Problem Based Learning (PBL) model. Carried out in three cycles, the results showed an increase in students' average scores from 48% in the pretest to 77% in Cycle III, meeting the target. PBL is effective in improving students' critical thinking, collaboration, and motivation skills. Obstacles faced include lack of student focus and time management. Suggested follow-up includes the development of interactive methods and improved guidance.